Participation of farm women in livestock management in Auraiya district of Uttar Pradesh - Singh, Brij Vikash; Kumari, Phool; Kumar, Anant; Singh, S.K. (Annals of Agricultural Research, 2017)
India occupies the fore most position in the world in respect of livestock contributing nearly aboutÂ¼ of the world total bovine population and women are the critical input in livestock management.Involvement of women in livestock management is a long standing tradition in India, where domesticanimals have been an integral part of the family system. Although most of the work related to dairyfarming is carried out by the women but their role has been ignored, Hence, the study on analysis ofdifferent roles performed by the rural women and the factor affecting them are of paramountimportance to the planners/decision makers (Government and extension workers) involved in thepresses of rural development. Keeping this fact in view, the present study has, therefore, beenpremeditated and undertaken in Auraiya district of Uttar Pradesh with specific objectives. Thefrequency of involvement of farm women was found highest in watering and feeding of animalfollowed by cleaning the cattle shed, cutting and bringing of fodder and compost making. Theresult indicated that with increasing the age of the farm women their involvement in livestockmanagement was decreasing. Whereas the education of the farm women was negatively significant(-0.8868) with their involvement in livestock management